2021
DOI: 10.1186/s40537-021-00434-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of deep learning image detection algorithms

Abstract: A computer views all kinds of visual media as an array of numerical values. As a consequence of this approach, they require image processing algorithms to inspect contents of images. This project compares 3 major image processing algorithms: Single Shot Detection (SSD), Faster Region based Convolutional Neural Networks (Faster R-CNN), and You Only Look Once (YOLO) to find the fastest and most efficient of three. In this comparative analysis, using the Microsoft COCO (Common Object in Context) dataset, the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(77 citation statements)
references
References 37 publications
0
76
0
1
Order By: Relevance
“…The YOLO-V3 network was trained using Google Colab [17], as it has a powerful graphics processing unit and more compute unified device architecture (CUDA) cores to reduce the overall training time [18]. It took around 5 to 6 hours for 2,000 iterations using 1,000 images of the required crop, which is to be detected 19], [20].…”
Section: Proposed Solutionmentioning
confidence: 99%
“…The YOLO-V3 network was trained using Google Colab [17], as it has a powerful graphics processing unit and more compute unified device architecture (CUDA) cores to reduce the overall training time [18]. It took around 5 to 6 hours for 2,000 iterations using 1,000 images of the required crop, which is to be detected 19], [20].…”
Section: Proposed Solutionmentioning
confidence: 99%
“…They compared Faster R-CNN with YOLOv3 and SSD and concluded that the YOLOv3 model is faster than both SSD and Faster R-CNN model and YOLOv3 has the best accuracy of 82% [42]. Moreover, several research efforts [61][62][63] conclude that a two-stage detector such as Faster R-CNN always has a better precision rate with a lower speed compared to a one stage-detector such as YOLOv5. Balancing the potholes detection accuracy and processing (inference) time is needed.…”
Section: Model-based Approaches For Potholes Detection Techniquesmentioning
confidence: 99%
“…In this study, we will only be using a 125 pair image dataset trained by the Faster-RCNN method. The Faster R-CNN method proves to be good for training on a small dataset [20]. The machine learning model will be trained using phyton programing language and detectron2 framework in the identity document card detection process.…”
Section: Faster R-cnn Detectionmentioning
confidence: 99%
“…The machine learning model will be trained using phyton programing language and detectron2 framework in the identity document card detection process. Detectron2 [20] is a module from Facebook with the weight of pre-trained Faster R-CNN architecture with the same base model as the original paper proposed [9].…”
Section: Faster R-cnn Detectionmentioning
confidence: 99%